Ridley. Season two [videorecording (DVD)] - Fisher, Jonathan (Producer); Thompson, Paul Matthew (PBS, 2024)
Retired Detective Inspector Alex Ridley is called back to advise on a complex and compelling murder case by his replacement and former protege DI Carol Farman. Carol is keen to access Ridley's unique insight into crime-solving which served them so well in the past, but the investigation takes a dark and unexpected twist.